Associations of parental reproductive age and elevated blood pressure in offspring: An observational study - Rui Deng; Ke Lou; Siliang Zhou; Xingxiu Li; Bin Dong; Jun Ma; Jie Hu (Frontiers Media S.A., 2023)
BackgroundIncreased parental reproductive age has been a social trend around the world, and elevated blood pressure in children leads to an approximately two-fold increased risk of hypertension in adulthood. Aim of this study is to assess the associations of parental reproductive age with the risk of elevated blood pressure in offspring, and to explore the influence of offspring lifestyle on the associations.MethodsData was obtained from a national school program conducted in 7 Chinese provinces, and the final sample was 39,190 students aged 7-18 years. Anthropometric measurements and questionnaires were designed to collect data of children blood pressure and information respectively.ResultsIn this study, 26.7% of children were defined as elevated blood pressure. A U-shaped pattern was observed in the relationship between maternal age and risk of elevated blood pressure, while risk of elevated blood pressure decreased continuously with paternal age increased. After adjustment, offspring of paternal age ≤27 & maternal age ≤26 years and those of paternal age >30 & maternal age >32 years were related to great risk of elevated blood pressure (OR = 1.18, 95% CI: 1.08-1.29, P < 0.001; OR = 1.18, 95% CI: 1.01-1.38, P < 0.05). When stratified by lifestyle status, significant associations between maternal/paternal age and risk of elevated blood pressure were only observed in those with worse lifestyle behaviors, but not in offspring with healthier lifestyle.ConclusionOur findings demonstrate that risk of elevated blood pressure in children is independently related to parental reproductive age, and children maintaining a healthy lifestyle may mitigate the adverse effect.